2016
DOI: 10.3415/vcot-15-04-0060
|View full text |Cite
|
Sign up to set email alerts
|

Lameness caused by an extradural lumbosacral foraminal synovial cyst in three German Shepherd Dogs

Abstract: Three German Shepherd Dogs that were presented for investigation of chronic unilateral hindlimb lameness and pain in the lumbosacral region were diagnosed with an intraspinal, extradural synovial cyst and reactive fibrosis protruding into the foramen of the lumbosacral articulation using magnetic resonance imaging and histology. This extradural mass compressed the nerve root in the foramen and the cauda equina. During a dorsal laminectomy and unilateral partial foraminotomy, the cyst and the fibrotic tissue we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Although spinal cysts have been described more frequently in veterinary literature in recent years, prevalence of canine arachnoid diverticula in the caudal lumbar region is very rare [ 1 , 10 ]. Schmöckel and Rapp [ 13 ] described a case series of synovial cyst at the lumbosacral junction in three German Shepherd dogs. One case, reported by Webb et al [ 12 ] and two dogs of a case series reported by Sale and Smith [ 16 ], presented a synovial/ganglion cyst associated with the L6–L7 articulations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although spinal cysts have been described more frequently in veterinary literature in recent years, prevalence of canine arachnoid diverticula in the caudal lumbar region is very rare [ 1 , 10 ]. Schmöckel and Rapp [ 13 ] described a case series of synovial cyst at the lumbosacral junction in three German Shepherd dogs. One case, reported by Webb et al [ 12 ] and two dogs of a case series reported by Sale and Smith [ 16 ], presented a synovial/ganglion cyst associated with the L6–L7 articulations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the aetiology of spinal cysts still remains unclear, theories are different between the various type of cysts/diverticula. Extradural cysts (of non-meningeal origin) were linked to increased mechanical stress and instability [ 2 , 4 , 12 , 13 , 16 ], whereas meningeal cysts are generally considered congenital lesions with a genetic predisposition [ 1 4 , 10 , 11 ]. However, SAD may also be acquired or traumatic, and seems to be related to concurrent spinal disorders like vertebral malformations and intervertebral disc disease [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A foraminotomy using endoscopically assisted instrumentation through a dorsal laminectomy can enlarge the inner part of the foramen, but the exit zone and the extraforaminal part of the L6 and L7 nerves cannot be addressed. A L7S1 traction-fusion procedure does not address extraforaminal pathologies (1, 4, 11) Moreover, the dorsolateral approach described by Gödde and Steffen allows the enlargement of the craniodorsal part of the L7 foramen, but the access is limited by the iliac wing (7). A partial, transverse iliac osteotomy removing the dorsal part of the ilium wing to increase the access has been described (12).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical signs vary according to location of the cyst and structures being compressed, e.g. : nerve roots or spinal cord, but there is a predominance of localized pain upon palpation of the vertebral column [46, 8]. Presumptive diagnosis is best achieved via MR imaging studies, where the cysts are well circumscribed lesions hyperintense on T2W images and hypo or isointense on T1W images [1].…”
Section: Introductionmentioning
confidence: 99%